Investigation on the integral effects of process parameters on properties of selective laser melted stainless steel parts - Choong, Yu Ying Clarrisa (2018)
In selective laser melting (SLM) process, several factors such as laser power, laser scanning speed and hatch spacing can affect the properties of the printed metal parts. The integral effects of all these parameters can be represented by the energy density which provides critical information to optimize the printing process. In this work, the influences of the process parameters on the density, roughness and hardness of stainless steel 316L parts printed using SLM 500HL were studied. The optimized printing parameters achieved high density, low porosity parts with improved mechanical properties. The use of the high-powered 700W laser from SLM 500HL also revealed an effective reduction in printing time without compensation in its mechanical properties.